2021
DOI: 10.1080/14656566.2021.1887140
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological considerations for the treatment of COVID-19 in people living with HIV (PLWH)

Abstract: Introduction When coronavirus infectious disease-2019 (COVID-19) blew up, ill-fated auguries on the collision between COVID-19 and the human immunodeficiency virus (HIV) epidemics loomed. Areas covered Data from observational studies suggest similar incidence attacks of SARS-CoV-2 infection in people living with HIV (PLWH) and HIV-uninfected populations. The mortality rate of COVID-19 is similar in both populations too. The authors discuss the role of combination antire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 150 publications
0
8
0
Order By: Relevance
“…Although dexamethasone, IL-6 inhibitors and JAK 1/2 inhibitors are recommended to treat COVID-19 pneumonia, within the HIV-infected population, there are no specific data for the use of such therapy. 111 126 127 128 129 130 Dexamethasone, ritonavir, and cobicistat are all metabolized by cytochrome P450 CA4, and whereas dexamethasone induces cytochrome P450 CA4 (CYP3A4) which can reduce ART levels, ritonavir and cobicistat are enzyme inhibitors which may increase the dose of corticosteroids with subsequent toxic effects 131 . Thus, ART drug levels should be monitored, not only with protease inhibitors and cobicistat but also with non-NRTIs, and only one dose of dexamethasone is recommended in combination with rilpivarine.…”
Section: Anti-inflammatory Therapymentioning
confidence: 99%
“…Although dexamethasone, IL-6 inhibitors and JAK 1/2 inhibitors are recommended to treat COVID-19 pneumonia, within the HIV-infected population, there are no specific data for the use of such therapy. 111 126 127 128 129 130 Dexamethasone, ritonavir, and cobicistat are all metabolized by cytochrome P450 CA4, and whereas dexamethasone induces cytochrome P450 CA4 (CYP3A4) which can reduce ART levels, ritonavir and cobicistat are enzyme inhibitors which may increase the dose of corticosteroids with subsequent toxic effects 131 . Thus, ART drug levels should be monitored, not only with protease inhibitors and cobicistat but also with non-NRTIs, and only one dose of dexamethasone is recommended in combination with rilpivarine.…”
Section: Anti-inflammatory Therapymentioning
confidence: 99%
“…NIPFC showed more than 36% antiviral activity against all tested viruses, with 60.61% antiviral activity against HIV (Supplementary Table S6). Based on antiviral prediction, it can be concluded that Bemcentinib, Bisoctriazole, and PYIITM can be used as potent antiviral drugs against the SARS-CoV-2 virus (Supplementary Table S5), because previous case and clinical studies suggested that some antiviral drugs mostly used for HIV showed effects against SARS-CoV-2 virus [31,32].…”
Section: In Silico Antiviral Predictionmentioning
confidence: 99%
“…The SARS-CoV-2 virus belongs to the β category of human coronaviruses [1][2][3], and its genomic organization is similar to that of other coronaviruses [4]. The viral genomic RNA (27)(28)(29)(30)(31)(32) codes both structural and non-structural proteins. The structural proteins include membrane (M), envelope (E), nucleocapsid (N), hemagglutinin-esterase (HE), and spike (S) proteins.…”
Section: Introductionmentioning
confidence: 99%
“…NIPFC showed more than 36% antiviral activity against all tested viruses with 60.61% antiviral activity against HIV (Supplementary Table S5). Based on antiviral prediction, it can be concluded that Bemcentinib, Bisoctriazole and PYIITM can be used as potent antiviral drugs against the SARS-CoV-2 virus (Supplementary Table S5), because in previous case and clinical studies suggested that some antiviral drugs mostly used for the HIV showed effect against SARS-CoV-2 virus [28,29].…”
Section: In Silico Antiviral Predictionmentioning
confidence: 99%
“…The SARS-CoV-2 virus belongs to the β category of human coronaviruses [1][2][3] and its genomic organization is like other coronaviruses [4]. The viral genomic RNA (27)(28)(29)(30)(31)(32) codes both structural and non-structural proteins. The structural proteins include: membrane (M), envelope (E), nucleocapsid (N), hemagglutinin-esterase (HE) and spike (S) proteins.…”
Section: Introductionmentioning
confidence: 99%